Analysis of Physical Water Quality in Griya Asri Housing District Fountain Stone Regency Deli Serdang - Meutia Nanda; Rahmadani Sagala; Rizky Nanda Pratama; Dhidy Haz Idiano; Ismi Larasati Hasibuan (Universitas Muhammadiyah Palu, 2024)
The physical quality of water can affect the physical condition of water, the physical condition of water can be in the form of smell, taste, color. There are several factors related to clean water that need to be considered, including sustainability, quantity and quality. This will be strengthened by access to clean water which is determined by how much clean water there is in the house and the surrounding environment. The aim of this research is to determine the physical quality of water in the Griya Asri residential area, Tuntungan District. The method used is a qualitative approach by conducting interviews with residents who live in the Griya Asri housing complex directly in the field. The research results show that there are two very broad aspects regarding the physical quality of clean water, the first is the environmental aspect, and the other is the health aspect. The physical availability of clean water in the Griya Asri residential area is not adequate because the water used is yellowish, smelly and rusty so that if used in daily life it has an impact on health. Lack of access to quality clean water is defined as a lack of availability of clean water, which is also caused by several factors, such as an uncertain climate and poor clean water storage infrastructure. To overcome this problem, a number of concrete actions are needed, such as creating other water sources and building infrastructure or water filters to increase access to the physical quality of clean water.